Esqueletos em quadrinhos: uma tradução comentada da poética de Zerocalcare - Aline Pereira Silva (2024)
This thesis discusses about the concept of comic books and the place that it holds in Contemporary Literature, presents the artwork of Zerocalcare, Michele Rech’s pseudonym, today’s most famous italian comic artist, and analyzes the poetics of his creation Scheletri (2020) through Peter Torop’s work La Traduzione Totale (2010), making use of this analysis to come up with an appropriate translation strategy for the graphic novel. Zerocalcare is the main character and tells a story from his youth, dealing with psychological issues, life in the suburbs, misogyny (especially when he witnesses an attempted feminicide) and homophobia, through an autofiction filled with references to pop culture and literature. In order to translate his work, it was first necessary to understand it in all its specificities and within the context illustrated by the author/character. At the end of this thesis, there is also an illustrated and commented translation of some scenes from the graphic novel Scheletri (2020).